SPIRITUALITY AS A POTENTIAL PSYCHOLOGICAL (PSYCAP) TOOL FOR FACING ACADEMIC STUDENTS IN ACCOUNTING STUDENTS - Wini Komalasari; Asep Kurniawan (JASS (Journal of Accounting for Sustainable Society), 2020)
This study presents the relevance of spirituality as a potential Psychological Capital of students pursuing a bachelor's degree in accounting to deal with academic stress, the condition of positive individual psychological development, consisting of variables of expectation, self-efficacy, resilience, and optimism. The data collected is a representative sample of 64 accounting students at STIESA and QUIZ who have responded to the survey. The results show that there is a significant influence between academic stress and spirituality